Automation using CAD for Gear, Sprocket And Splines Hob Cutter Manufacture - Singh, Gurjinder Pal (My University, 2013)
Gears are widely used product in manufacture of machines. Their application is everywhere we need to transmit power with high efficiency from one point to other. The most common methods for gear cutting are hobbing, milling, rack cutting. The latest trend of the high scale industries is the knowledge base design automation. Using the CAD Automation any user can generate desired gear profile more accurately through the automated design software by defining the proper relation between the parameters. This automation is attempt to do elimination of the manual drawing along with the conventional machines for generation of gear to cutter profiles used by the optical profile grinder if the profile matches then grind the form tool cutter profile using which the hob cutter will be made used in manufacturing tool industry. Thus the industry requires automation in generation of gear to cutter profile which is normally done manually. Incorporation of parametric CAD softwares is used for the generation of gear to cutter profile with relating the various parameters of gear terminology. This technique gives high accuracy and possible to produce high quality cutters. Further this CAD software automation is attempt to make the macros for generating the required profiles i.e cutter profiles and tracing them with the use of API (Application Program Interface) for the actual use in manufacturing process. Work has been done on various kind of profiles like gear cutter profiles, sprocket cutter profiles, spline cutter profiles, chamfered spline cutter profiles and rack to gear profile generation.
ME, MED
Keywords: CAD Automation, API, Gear Hob Manufacture, Sprocket Hob Manufacture, Spline Hob Manufacture